New Technologies' Commercialization: The Roles of the Leader's Emotion and Incubation Support - Shan, Biaoan; Pu, Yi; Chen, Biao; Lu, Shan (Frontiers in Psychology, 2021)
New technologies, such as brain-computer interfaces technology, advanced artificial intelligence, cloud computing, and virtual reality technology, have a strong influence on our daily activities. The application and commercialization of these technologies are prevailing globally, such as distance education, health monitoring, smart home, and robots. However, we still know little about the roles of individual emotion and external environment on the commercialization of these new technologies. Therefore, we focus on the emotional factor of the leader, which is their passion for work, and discuss its effect on technology commercialization. We also analyzed the moderating role of incubation support in the relationship between the leader emotion and technology commercialization. The results contribute to the application of emotion in improving the commercialization of new technologies.